AN ANALYSIS OF ENGLISH TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION - Yulia Enggar Wigati Wibowo; Syafrizal Syafrizal; Syafryadin Syafryadin (JALL (Journal of Applied Linguistics and Literacy), 2020)
The objective of this research is to find out the teachers’ strategies in teaching reading comprehension at one of Senior High School in Bengkulu, Indonesia. This research is mixed-method research design. The subjects in this research are two English teachers who teach English at class X, XI, and XII. The data were collected using an observation checklist. The result of the research showed that the teachers used some strategies in teaching reading with the highest percentage were Question Generating (27%), Encouraging the Use of Dictionaries (25%) and Question Answering (23%). This indicated that the teachers only used a few strategies in teaching reading comprehension. For the next researchers, they could conduct research about the teachers’ strategies used by English teachers in a wider area. So, the result will be more advantageous and be applied in a larger area.Keywords: Teachers’ Strategies, Reading Comprehension